Association of Serum Magnesium with Preterm Labor (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
In recent years preterm labor is a significant obstetric concern. Alteration of basic biochemical function at cellular level is one of the etiologies of preterm labor. Several trace elements including magnesium are associated with normal cellular function. Magnesium sulfate is used as a tocolytic agent because high magnesium level causes relaxation of smooth muscle. Hypomagnesaemia leads to neuromuscular irritability leading to uterine hyperactivity which leads to cervical dilation. Therefore, this study was performed to find out the association of hypomagnesemia with preterm labor. This cross-sectional study was conducted in 100 women in labor, of them 50 were diagnosed case of preterm labor and 50 women were in labor at term attended in BSMMCH, Faridpur during July 2021 to December 2021. After overnight fasting 5ml blood sample was collected and was analyzed for serum magnesium using standard enzymatic method. Mean value of serum magnesium was compared between two groups by student unpaired t-test. A p-value was considered to be statistically significant at 0.05 at the 95% confidence interval. The mean serum magnesium was found 1.44±0.36 mg/dl in preterm labor and 2.0±0.27 mg/dl in term labor. Low serum magnesium level was significantly higher in preterm labor.Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 45-48